Oligo(metallocene)s Containing Keto‐Bridged Phospholyl Rings. Issue 10 (19th December 2013) - Carmichael, Duncan; le Goff, Xavier‐Frédéric; Muller, Eric
Abstract: A chiral racemic tris(phosphaferrocene) complex showing two bridging keto functionalities has been prepared diastereoselectively through the elaboration of a single 2, 5‐diester‐substituted phosphaferrocene. The reaction profile involves the intervention of a single trinuclear complex, which contains two phosphametallocene units and an η 1 ‐coordinated phospholyl ligand9, whose organisation determines the stereochemistry of the final product. This complex evolves smoothly to give a chiral triphosphametallocene (±)‐( R *, R *)‐[2, 5‐(2′‐CO2 Me‐3′, 4′‐Me2 PC4 ‐FeCp*)‐(η 5 ‐Me2 PC4 )FeCp*]10 . Abstract : The homologation of a 2, 5‐diester substituted phosphametallocene into a 2′, 5‐diester substituted triphosphametallocene array is presented. The high stereochemical selectivity for the (±)‐( R *, R *) configured triphosphametallocene product is shown to result from an autotemplation of the reaction pathway.